Qualidade de vida em doenças pulmonares crônicas: aspectos conceituais e metodológicos - Ramos-cerqueira, Ana Teresa De Abreu [UNESP] (2000)
The present article purports to analyze aspects related to the concept of quality of life, taking into account the relevance of setting down parameters that allow for the evaluation of those aspects, especially in patients with chronic diseases. The analysis considered quality of life as one of the essential components of medical care, and pointed out the precautions that should be taken to choose instruments of evaluation, that should be sensitive and reliable to the dimensions they intend to evaluate.